International reserves management and the current account - Joshua Aizenman (University of California, Santa Cruz Institute for International Economics (SCIIE), 2006)
The paper assesses the costs and benefits of active international reserve management (IRM), shedding light on the question of how intense should IRM be for an emerging market. In principle, an active IRM strategy could lower real exchange rate volatility induced by terms of trade shocks; provide self insurance against sudden stops; reduce the speed of adjustment of the current account; and even allow for higher growth if it fosters exports (mercantilist motive). The message of the report is mixed management of reserves is not a panacea. The mercantilist case for hoarding international reserves, as an ingredient of an export led growth strategy, is dubious. Done properly, IRM augments macro economic management in turbulent times, mitigating the impact of external adverse shocks and allowing for a smoother current account adjustment. These benefits are especially important for commodity exporting countries, and countries with limited financial development.
Keywords: 330; Währungsreserven; Währungsmanagement; Zahlungsbilanz; Exportinduziertes Wachstum; Aufstrebende Märkte